Effect of the Tool to Reduce Inappropriate Medications on Medication Communication and Deprescribing. Issue 10 (14th August 2017) - Fried, Terri R.; Niehoff, Kristina M.; Street, Richard L.; Charpentier, Peter A.; Rajeevan, Nallakkandi; Miller, Perry L.; Goldstein, Mary K.; O'Leary, John R.; Fenton, Brenda T.
Abstract : Objectives: To examine the effect of the Tool to Reduce Inappropriate Medications (TRIM), a web tool linking an electronic health record (EHR) to a clinical decision support system, on medication communication and prescribing. Design: Randomized clinical trial. Setting: Primary care clinics at a Veterans Affairs Medical Center. Participants: Veterans aged 65 and older prescribed seven or more medications randomized to receipt of TRIM or usual care (N = 128). Intervention: TRIM extracts information on medications and chronic conditions from the EHR and contains data entry screens for information obtained from brief chart review and telephonic patient assessment. These data serve as input for automated algorithms identifying medication reconciliation discrepancies, potentially inappropriate medications (PIMs), and potentially inappropriate regimens. Clinician feedback reports summarize discrepancies and provide recommendations for deprescribing. Patient feedback reports summarize discrepancies and self‐reported medication problems. Measurements: Primary: subscales of the Patient Assessment of Care for Chronic Conditions (PACIC) related to shared decision‐making; clinician and patient communication. Secondary: changes in medications. Results: 29.7% of TRIM participants and 15.6% of control participants provided the highest PACIC ratings; this difference was not significant. Adjusting for covariates and clustering of patients within clinicians, TRIM was associated with significantly more‐active patient communication and facilitative clinician communication and with more medication‐related communication among patients and clinicians. TRIM was significantly associated with correction of medication discrepancies but had no effect on number of medications or reduction in PIMs. Conclusion: TRIM improved communication about medications and accuracy of documentation. Although there was no association with prescribing, the small sample size provided limited power to examine medication‐related outcomes.